DARI ‘MUHLAL’ HINGGA ‘MUHRABI’ (Tipologi Pemikiran Hadits Hisab-Rukyat di Kalangan Muhammadiyah) - Ali Imron; Syamsul Hadi; Syamsul Anwar; Agung Danarto (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
This paper corrects the assumption which thinks that Muhammadiyah is a social organisation which putting forward the absolute hisab in deciding the beginning of the month. By using typology and analytical descriptive method in undestanding the dynamic decision and determination of the beginning of Hijriyyah months (especially Ramadhan, Syawal, and Dzulhijjah). Thus, the paper shows that actually in Muhammadiyah there are various hisab-rukyat tipology of thinking. There are six kinds hisab-rukyat tipology of thinking in Muhammadiyah. They are (a) 'Muhlal' group (Muhammadiyah-Wujudul Hilal); (b) 'Muhkayat' group (Muhammadiyah-Imkanur Rukyat); (c) 'Muhpem' (Muhammadiyah-Pemerintah); (d) 'Muhyata' ('Muhammadiyah-Rukyat Semata); (e) Muhijar ('Muhammadiyah-Ijtima' Qabla Fajar'), (f) ‘Muhrabi’ (Muhammadiyah-Arab Saudi). Each group represent the tendency and non-single dynamic in understanding Hadits of the prophet in deciding the beginning of the month. This is very interesting to analyze because the dynamic did not happen in any other social organizations which tend to be similiar in deciding the beginning of the month. As a social organization which is not only big in quantity but also in quality with many rational Muhammadiyah followers/youngster, the different way of thinking will still happen although the main stream will still be hold or even won by certain group.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.733